Philosophical perspectives of music education - Allsup, Randall; Arroyo, Margarete [UNESP]; Cardoso, Renato de Carvalho [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2018)
This is the translation of the chapter written by Randall Allsup, Philosophical Perspectives of Music Education, published in 2010 in the book Critical Issues in Music Education edited by Abeles, H.J. and Custodero, L. The field of philosophy of musical education, which counts with a significant production in English, still has little presence among Brazilian researchers. Allsup is lecturer at Teachers College of Columbia University in courses linked to creativity and solving problems, democracy and music education and philosophy of musical education.
Keywords: Philosophy of Musical Education; Preparing musical educators; Educators-Philosophers